PMMA/double-modified organoclay nanocomposites as fillers for denture base materials with improved mechanical properties. (February 2019) - Shakeri, Fateme; Nodehi, Azizollah; Atai, Mohammad
Abstract: The aim of this study was to investigate the effect of double-modified organoclay on mechanical properties of polymethylmethacrylate (PMMA) denture base resins. An organoclay was further modified via a silanization process using 3-trimethoxysilylpropyl methacrylate (MPS) as a reactive silane coupling agent. X-ray diffraction patterns (XRD), thermogravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FTIR) confirmed the presence of MPS in the resulting double-modified nanoclay structure. Surface tension of the original and double-modified nanoclays, were determined using contact angle measurements. Results showed that double-modified nanoclay has more organophilic nature due to silanization of the clay edges. Free radical suspension polymerization of methylmethacrylate monomers in the presence of different amounts of double-modified organoclay was performed and PMMA/clay nanocomposites were obtained. Results of dynamic mechanical thermal analysis (DMTA) showed increased storage modulus and glass transition temperature for the resulting nanocomposites with respect to neat PMMA. Higher improvements in storage modulus and glass transition temperature were obtained for nanocomposites containing 0.25 and 0.5 wt% of double-modified nanoclay. TEM observations of the nanocomposite containing 0.5 wt% of double-modified nanoclay showed prevailing exfoliated morphology. Aforementioned nanocomposites with higher mechanical properties were incorporated into a denture base formulation and their mechanical properties were studied using static flexural and fracture toughness tests. According to the results, both reinforced samples showed increased flexural strength, flexural modulus and fracture toughness in comparison to the neat matrix. The average improvements in flexural strength, flexural modulus and fracture toughness were about 30%, 65.8% and 32%, respectively. Scanning electron microscopy (SEM) images of the fracture surface of the resin matrices subjected to static tests showed brittle and ductile surface fracture for neat and reinforced denture base specimens, respectively.